The Influence of Negative Symptoms on the Social Function of People with Schizophrenia in the Community - Warih Andan Puspitosari; Soewadi Soewadi; Sumarni Sumarni (Berkala Kedokteran, 2018)
Abstract: The most People with Schizophrenia (PwS) experience a decline in social function caused by various factors. Clinical symptoms of PwS affect the social function of PwS, especially negative symptoms. The purpose of this study is to analyze the effect of negative symptoms on the social function of people with schizophrenia in the community. This is a cross-sectional study. Subjects of the study were people with schizophrenia aged 18-56 years who will follow Community-Based Rehabilitation activities in 10 areas of puskesmas in Yogyakarta Special Region. The study was conducted in February 2017. The social function and negative symptoms of PwS were measured using a validated measuring instrument. Hypothesis test using Anova test. The subjects of the study were obtained by purposive sampling technique of 100 PwS that fulfilled inclusion and exclusion criteria. Subjects with a PSP score of 0-30 (poor: someone who intensively needs care and social support) of 8 people (8%) had negative PANSS score of 28.50 ± 6.78. Subjects with a score of 31-70 (moderate: someone who occasionally needs care and social support) of 57 people (57%) had negative PANSS of 20.65 ± 8.18. Subjects with a score of 71-100 (mild: someone with mild disturbance, but able to perform individual functions) of 35 subjects (35%) had negative PANSS score of 12.49 ± 5.98. PwS which has a negative value of PANSS is greater, has a worse social function. The results showed that the negative symptoms had an effect on the social function of people with schizophrenia which was statistically significant (p <0.05). Negative symptoms affect the social function of PwS. PwS that has a high negative symptom score, has a worse social function. Keywords: social function, schizophrenia, negative symptoms